Strategi Pemasaran Desa Wisata Bonjeruk - Lalu Adi Permadi; Hj. Hilmiati Fauzi; Emilia Septiani (Universitas Mataram, 2021)
This research aims to design the proper marketing strategy for Bonjeruk Tourism village. Data used in the research are primary and secondary data. Primary data were mainly obtained by interviewing the local stakeholder. On the other hand, secondary data were taken from library studies and government data. This research suggested the main strategies that can be implemented in marketing Bonjeruk tourism village are Product and Promotion Strategies. Product Strategies are 1) Brand Strategy with Historical Tourism Village Branding, 2) Tourism Village Product Development Strategy with agro and natural tourism as alternatives and Maintaining History and Culture as Main Tourism Attractions and 3) Strategy to improve the quality of Historical and Cultural packages diversify non-historical and cultural tourism objects. Other promotion strategies that can be used are the use of the internet and social media to promote and utilizing stakeholders, including Bonjeruk residents, Bonjeruk residents outside the village, and tourists, to create e-WOM (electronic Word of Mouth).